DEVELOPMENT AND INITIAL VALIDATION OF THE SECOND VERSION OF THE MULTIDIMENSIONAL SOCIAL CAPITAL SCALE (MSCS V2) - Maķevica, Dina; Šuriņa, Sanita; Perepjolkina, Viktorija; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
This article describes the development and initial validation of the second version of the Multidimensional Social Capital Scale (MSCS V2). The scale is based on the concept of Social Capital (SC) developed based on the results of the Rapid Review. The developed theoretical concept covers such types of SC as bonding, bridging, and linking, and there are two dimensions in each of these types: cognitive and structural. The initial version of the Multidimensional Social Capital Scale (MSCS) covered only the cognitive dimension of all three types of SC. This study aimed to develop an improved second expanded version of the MSCS V2 and to evaluate its psychometric properties. Data were collected online in the period from 11th June to 3rd October 2021, using a cross-sectional study design and a convenience sample strategy (N=353, 87% women and 13% men), aged between 18 and 80 years, M=41.8 years). As a result, the 25-item version of the MSCS V2 was developed. Exploratory factor analysis (EFA) revealed a 6-factor structure that encompasses the following types and elements of cognitive dimension: two types of bonding (Perceived social support or family members and close friends and Sense of belonging), two types of bridging (Perceived social support for acquaintances and General social trust), one type of linking (Institutional trust) and for Structural dimension: one type of bonding (Social participation). This 6-factor structure was approved using confirmatory factor analysis (CFA). Overall, the items are internally consistent on all scales (α = .73 - .90). Findings from this study showed significant evidence for the reliability and validity of the MSCS V2 and it would be advisable to repeat the study in a homogeneous sample, including full socio-demographic data.